Literature Review : Effect of Herbal Plant Extracts Containing Tannins on Histopathological Kidney of Diabetic Rats - riza, salim; Etty Widayanti; Aan Royhan (Fakultas Kedokteran Universitas YARSI, 2023)
Hyperglycemia is a disorder of carbohydrate metabolism characterized by high blood glucose levels. Hyperglycemic treatment is usually done by administering oral hyperglycemic drugs. Therapy using drugs, either in the form of oral anti-diabetic drugs, insulin therapy, or a combination of both. Herbal medicine can be an alternative treatment in the treatment of hyperglycemia. Various types of extracts from various parts of several medicinal plants have been tested for hyperglycemic activity, one of which is due to the content of tannin compounds. The purpose of this study was to determine the effect of herbal plant extracts containing tannins on the histopathological of the kidneys of diabetic rats. The research method uses the Literature Review method with secondary data collection from scientific research articles from 2019-2023. Search data using the online Google Scholar database using key words such as tannins, diabetes, histopathology, kidney and rats. Articles are then evaluated based on the title and abstract. From the 5 results of this Literature Review, all literature states that there is an effect of herbal plant extracts containing tannins on the histopathological of the kidneys of diabetic rats.